The solo ngawi toll road investment evaluation and risk assessment - Fachriansyah, M. Fadhil; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2016)
Abstract - The toll road is required by government to support the economic growth. In the implementation, the toll road uses one of the strategies through the Build-Operate-Transfer (BOT) Public â€“ Private-Partnership (PPP) scheme to attract the private sector. The financial feasibility in the toll road project mostly are influenced by traffic, tariff, and construction. Those three elements and the other factors affect the project financing outcome for the 35 years concession period. In this research, the financial feasibility will be analyzed based on the loan tenor for project fund (10 years and 15 years) and the construction schedule (2 years and 2.5 years). The analysis outcome of the third alternative of loan tenor 15 years and construction schedule 2 years is more attractive than other alternatives. The investment parameter express the positive NPV value for IDR 184,028 (in million) and the IRR value more than WACC value (19.20% > 17.58%). The other financial analysis also express that the third alternative has better output such as debt to equity ratio (DER) value is 1.33 which is lowest than others; and operating profit margin is 0.75, higher than the other alternatives.Â  Keywords: BOT-PPP scheme, investment evaluation, loan tenor, construction schedule, risk assessment.